Modelling Ecological Risk Assessment Using Temporal Intuitionistic Fuzzy Sets for Corrosion Impact Assessment (International Journal of Environmental Sciences, 2025)
This study proposed a novel division operation over Intuitionistic Fuzzy Sets to assess its decision-making properties. The study extends Intuitional Fuzzy Sets (IFS) by integrating temporal properties to perform operational functions in order to enhance the decision-making process. We modeled different causes of corrosion using Intuitionistic Fuzzy Set (IFS) to predict the corrosion type within four chosen villages (). We estimated the normalized Hamming distances among different corrosion profiles and its causes to quantify which type of corrosion pose serious threat to the village. The results show that TIFSs effectively resolve uncertainties in decision-making, particularly in cases where traditional fuzzy set methods produce ambiguous outcomes, where FS failed to distinguish between wind and water corrosion for village ????3, the TIFS-based approach provided a clear classification. Our findings suggest that TIFS-based framework is robust to address the ecological risks paving way for management interventions. However, fuzzy sets representing membership values and intuitionistic fuzzy sets for connection and non-connection value fail to yield consistent outcomes.